1973
DOI: 10.1107/s0567740873002013
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of tropolone

Abstract: Tropolone, C7H602, crystallizes in space group P21/e, with a= 7.135, b---12.178, c= 7.122 A, fl= 99.63 ° and Z= 4. The crystal structure was solved by the symbolic addition procedure and refined by the leastsquares method to give the final R value of 0.054 for the 853 observed reflexions. The molecule is essentially planar and exhibits a slight degree of bond alternation in the seven-membered ring. The hydroxyl group makes a bifurcated hydrogen bond with carbonyl oxygen atoms, of which one branch is intramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
67
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 20 publications
12
67
0
Order By: Relevance
“…The carbonoxygen bonds are also involved in the electron delocalization as indicated by the lengths, C(1)-O(1)=1-261 and C(2)-O(2)= 1"349 A. A revised report on the tropolone structure, based on re-measured intensities, has now appeared (Shimanouchi & Sasada, 1973). This indicates that there is in fact bond-length alternation in the ring, in agreement with the situation in IPT.…”
Section: Olji-p-o'111supporting
confidence: 60%
See 1 more Smart Citation
“…The carbonoxygen bonds are also involved in the electron delocalization as indicated by the lengths, C(1)-O(1)=1-261 and C(2)-O(2)= 1"349 A. A revised report on the tropolone structure, based on re-measured intensities, has now appeared (Shimanouchi & Sasada, 1973). This indicates that there is in fact bond-length alternation in the ring, in agreement with the situation in IPT.…”
Section: Olji-p-o'111supporting
confidence: 60%
“…Shimanouchi & Sasada (1973) noted that the ring in tropolone adopts a boat conformation similar to, but shallower than, that observed for a number of tropones. In the tropones, the 'boat' is described in terms of the planes defined by the three groups of atoms C(1,2,7), C(2,3,6,7) and C (3,4,5,6), and these same groups of atoms were used to describe the boat conformation of the tropolone ring, the r.m.s, atomic deviations being 0, 0-009 and 0.007 /~, respectively.…”
Section: Olji-p-o'111mentioning
confidence: 99%
“…The title compound consists of a tropolone core with three methyl morpholine moieties bound to it at C3, C5 and C7 of the backbone, with additional water (0.67 occupancy) completing the asymmetric unit, as shown in the gure. Earlier in the 1970′s, Shimanouchi et al reported the molecular structure of tropolone [10,11]. When comparing this structure to that of tropolone, some slight deviations were observed within the tropolone core.…”
Section: Discussionmentioning
confidence: 99%
“…Bond lengths and angles involving hydrogen atoms 1968; Ibata, Hata, Shimanouchi & Sasada, 1972;Shimanouchi & Sasada, 1973) and by an SCM MO method (Dewar & Trinajsti6, 1970a, b) has a sevenmembered ring with a marked boat form with the planes of the two benzene rings inclined to each other at an angle of about 39 ° . It appears that when benzene rings are fused to the tropone ring there is a large dihedral angle while five-membered rings give planar molecules.…”
Section: Table 3(a) Distances Of Atoms (X 10 A) From Some Best Leastmentioning
confidence: 99%